The copper grade estimation of porphyry deposits using machine learning algorithms and Henry gas solubility optimization - Abbaszadeh M.; Ehteram M.; Ahmed A.N.; Singh V.P.; Elshafie A. (Springer Science and Business Media Deutschland GmbH, 2023)
algorithm; copper; electrical conductivity; estimation method; machine learning; optimization; ore deposit; ore grade; porphyry; solubility; Iran; Kerman [Iran]